Synthesis of substituted biphenyls and in vitro evaluation of antimicrobial and anti-biofilm activities supported by in silico ADMET prediction - Saad Alghamdi; Ahmed Hassen Shntaif; Yasser Hussein Issa Mohammed (PLoS ONE, 2026)
Antibiotic resistance represents a critical global health challenge, necessitating the development of innovative antimicrobial agents. This research focuses on the design and evaluation of antimicrobial compounds through chemical synthesis and computational methodologies. Biaryl analogues were synthesized via Suzuki coupling reactions and assessed for in vitro antimicrobial activity against Staphylococcus aureus , Escherichia coli , and Candida albicans . Computational approaches, including molecular docking, crystal structure optimization, and toxicity profiling, were employed to explore potential molecular interactions and preliminary safety profiles. The synthesized biaryl derivatives demonstrated variable antimicrobial activity across the tested microorganisms. Among these, 2-methoxy-4’-nitro-1,1’-biphenyl (3i) exhibited the most potent antibacterial activity against both Gram-positive and Gram-negative strains. As a preliminary screening, these findings highlight the potential of selected biaryl derivatives as lead candidates for further investigation. Future studies are required to validate activity against resistant strains and to evaluate efficacy in vivo .